Rethinking imperfections in tanks and silos. (13th September 2017) - Knoedel, Peter; Ummenhofer, Thomas; Rotter, J. Michael
ABSTRACT: A careful consideration of imperfections is critical to the design of shell structures to ensure that they are both adequately safe and economically built. Following the development of the Eurocode for shell structures EN 1993‐1‐6, the situation has considerably improved: the extensive literature on the imperfection sensitivity of shells has been introduced into practical designs; fabrication tolerance classes have been defined, which allow the designer to adjust his design to the professional efforts of the fabricator; and numerical and experimental results have been matched by defining an axisymmetrical weld depression as a substitute imperfection in the recent amendment. These advances seem to have established a very good position, and it might be thought that little more needs to be done. However, a closer look at some of the above items reveals the need to reconsider the management of imperfections, especially from the designers point of view. In this paper the authors attempt to make a first step to resolve the role of imperfections from different points of view. In addition, some unpublished results from researches at KIT are presented.